The Physical Basis of Nuclear Weapon Design - Zhan, Aiming (Transactions on Computer Science and Intelligent Systems Research, 2024)
This document delves into the theoretical foundation and design principles of nuclear weapons, commencing with an exploration of the characteristics of fissile materials. Due to the high level of confidentiality of nuclear weapons, their specific details cannot be known by the vast majority of people, but this article focuses solely on their theoretical analysis. It elucidates the fundamental mechanisms of nuclear reactions, introducing the concept of nuclear criticality—the point at which a chain reaction can be sustained. Through intricate mathematical modeling, it describes the diffusion patterns of neutrons within nuclear fuel and surrounding reflector layers. Furthermore, the article presents a comprehensive design approach required to attain a supercritical state, inclusive of a driving apparatus and remote control systems. A pivotal component discussed is the neutron tube, which serves as the primary source of initiation neutrons. In essence, this paper offers profound insight into the sophisticated mechanics and operational principles underlying nuclear armament design.